2005
DOI: 10.1007/s00405-005-1007-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hearing aid use over the past 20 years

Abstract: The aim of this study was to find out how the use of hearing aids has been affected by the changes in hearing rehabilitation, hearing aids and society over the past 20 years. Seventy-six first-time hearing aid users were interviewed at their homes, and the results were compared with those of an earlier study made with the same method in 1983 in Finland involving both new and experienced hearing aid users. Hearing aid use and handling skills as well as satisfaction with the hearing aid were explored with interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Compared to the results of studies from other countries, use, satisfaction and management rates for unilaterally fitted persons and owners of simple devices must be still considered excellent (Dillon et al, 1999;Lupsakko and Kautiainen, 2005;Parving, 2003;Smeeth et al, 2002;Smith et al, 2005;Stark and Hickson, 2004;Stephens et al, 2001;Stock et al, 1997;Uriarte et al, 2005;Vuorialho et al, 2006). It appears that the Swiss hearing aid dispensing model with a careful comparative fitting and continued counselling after the initial fitting has contributed substantially to the high regular-use, satisfaction and management rates regardless of the signal processing 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 are not limited to the degree of hearing loss but include non-audiometric factors such as the handicap resulting from hearing loss, may also have contributed to the results.…”
Section: The Swiss Model Of Hearing Aid Provisionmentioning
confidence: 99%
“…Compared to the results of studies from other countries, use, satisfaction and management rates for unilaterally fitted persons and owners of simple devices must be still considered excellent (Dillon et al, 1999;Lupsakko and Kautiainen, 2005;Parving, 2003;Smeeth et al, 2002;Smith et al, 2005;Stark and Hickson, 2004;Stephens et al, 2001;Stock et al, 1997;Uriarte et al, 2005;Vuorialho et al, 2006). It appears that the Swiss hearing aid dispensing model with a careful comparative fitting and continued counselling after the initial fitting has contributed substantially to the high regular-use, satisfaction and management rates regardless of the signal processing 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 are not limited to the degree of hearing loss but include non-audiometric factors such as the handicap resulting from hearing loss, may also have contributed to the results.…”
Section: The Swiss Model Of Hearing Aid Provisionmentioning
confidence: 99%
“…Despite evidence that hearing-aid use can ameliorate some of the negative consequences of hearing loss (Chisolm et al, 2004;Chisolm & Arnold, 2012;Mulrow et al, 1990), the charity Action On Hearing Loss estimate that, although 2 million people in the UK have hearing aids, only 1.4 million use them regularly. This is supported by surveys of hearing-aid use with estimates of non-use varying from 5-40% (Gimsing, 2008;Hougaard & Ruf, 2011;Kochkin, 2000;Lupsakko et al, 2005;Smeeth et al, 2002;Vuorialho et al, 2006). Thus, the behaviour of interest in this case is the regular, long-term use of hearing aids by adults with acquired hearing loss.…”
mentioning
confidence: 73%
“…We identified several individual studies reporting rates of hearing aid use and non-use [6][7][8][9][10][11][12][13] and two recent systematic reviews that summarise reported reasons for non-use [26,27]. We used the COM-B model to categorise reasons for non-use reported in these reviews.…”
Section: Step 1-define the Problem In Behavioural Termsmentioning
confidence: 99%
“…The low level of uptake of hearing healthcare services represents a public health issue which we felt others were better able to address. Estimates of hearing aid non-use amongst adults with acquired hearing loss vary from 5 to 40 % [6][7][8][9][10][11][12][13]. The true extent of non-use is open to debate since different methods of data collection and different lengths of follow-up cloud the picture.…”
Section: -Define the Problem In Behavioural Termsmentioning
confidence: 99%
See 1 more Smart Citation